2004
DOI: 10.1080/11250000409356633
|View full text |Cite
|
Sign up to set email alerts
|

Basic morphological data and notes on natural history and conservation of a populationof Emys orbicularisin southern Apulia (Carovigno, Salento)

Abstract: A population of Emys orbicularis hellenica (Valenciennes, 1832) from the coastal pond of Pantanagianni was studied for two years using capture-mark recapture methods; 57.1% of specimens were females, 32.1% males, and 10.8% immature. For every specimen captured, a series of biometric parameters were applied and information relating to phenotypic characteristics was gathered. The statistically analysed data, from twenty-five sexually mature animals, clearly showed evident sexual dimorphism, with lighter males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 1 publication
5
8
1
Order By: Relevance
“…In comparing the results of these differing parameters, mass, length, height and width of the shell highlighted the importance of their role in the sexual dimorphism of the species (Fattizzo, 2004), which is in agreement with our observations. In agreement with the results obtained by Mazzotti (1995) and Zuffi and Gariboldi (1995b), significant differences were found between males and females in shell height (SH).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In comparing the results of these differing parameters, mass, length, height and width of the shell highlighted the importance of their role in the sexual dimorphism of the species (Fattizzo, 2004), which is in agreement with our observations. In agreement with the results obtained by Mazzotti (1995) and Zuffi and Gariboldi (1995b), significant differences were found between males and females in shell height (SH).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with the results obtained by Zuffi & Gariboldi (1995b) and Fattizzo (2004), a comparison between the ratio and the difference between the TL/PL and PL-TL showed that in males the tail was longer with respect to the length of the shell. The considerably larger CT/TL ratio in the females, and TL-CT in the males, clearly confirmed the role that the presence of the penis had in determining the longer length in the first part of the tail of the males, and its application to the determination of sex in this species.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, large‐scale bias from introduced turtles is unlikely. In agreement with their mitochondrial haplotypes, the very most turtles from southern Apulia are morphologically typical representatives of E. o. hellenica (Fattizzo ), irrespective of a genotypic impact of E. o. galloitalica . This suggests either largely male‐mediated gene flow from E. o. galloitalica into E. o. hellenica or selection against hybridization in the opposite direction.…”
Section: Discussionmentioning
confidence: 53%
“…While there are many admixed individuals or genotypically pure E. o. galloitalica with hellenica haplotypes, there is not a single genotypically pure E. o. hellenica with galloitalica haplotypes, and this is also true for southern Apulia and Basilicata (Fig. : sites 23–27) where pond turtles are still widely distributed and quite common (Fattizzo ). Thus, large‐scale bias from introduced turtles is unlikely.…”
Section: Discussionmentioning
confidence: 99%